Paradygmaty społecznego ubezpieczenia emerytalnego wykład inauguracyjny na Uniwersytecie Wrocławskim, rok akademicki 2014/2015 - Kalina-Prasznic, Urszula (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Living up to old age is probable but uncertain. Every generation tried to find ways to minimise negative, both biological and economic, effects of old age, when people lose their abilities and possibilities to earn money. This gave rise to the old age pension insurance. It is based on paradigms, i.e. specific social and economic rules, defining an attitude towards older people, level of solidarity between generations and public authorities’ social functions. The reforms conducted in the 1990s in most of the post-socialist countries deeply changed the rules of organisation and functioning of old age pension systems as well as their roles in the society. The key paradigms, i.e. insurance reciprocity based on solidarity and collective prudence, were rejected and replaced with the idea of non-solidarity “everyone is responsible for themselves”, which involves privatisation of pension risk and making an individual bear the consequences of loss of earnings upon reaching retirement age.
Keywords: ubezpieczenie emerytalne